ANALISIS MODEL PENILAIAN BERBASIS TEKNOLOGI DIGITAL UNTUK MENGUKUR PERILAKU KEJUJURAN MAHASISWA - Susilawati, Evi; Khaira, Imamul; Ali, Ali; Adlina, Zuraidah; Afnaria, Afnaria (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2023)
The aim of this research is to carry out an analysis of the validation test on the digital-based assessment model design of Automated Short Essay Scoring (ASES) to MEASURE student honesty behavior in the Pancasila and Citizenship Education Study Program, Faculty of Teacher Training and Education (FKIP), Universitas Islam Sumatera Utara (UISU). ). The research method used in this research uses the research and development model by Borg and Gall which focuses on the analysis and validation test stages of the Automated Short Essay Scoring (ASES) assessment model to measure the increase in student honesty behavior. This research uses indicators of honesty behavior in sub-indicators; (1) pleasant behavior, (2) stating what is (3) maintaining the truth, (4) fulfilling obligations and receiving rights, (5) keeping promises. The results of this research show that based on analysis and validation tests from psychology experts, it can be stated that the ASES digital technology-based assessment model is declared valid and can be used to measure the honest behavior of students in the PPKN Study Program, FKIP UISU